(untitled) (KULT_online, 2017)
Based on a research workshop at Friedrich Schiller University Jena, the volume Heimat gestern und heute features essays and critical responses from a wide range of disciplines. Scholars of musicology, literary studies, pedagogy of religion, European ethnology, folklore studies, history, law, human geography, and botany offer perspectives on changing notions of Heimat. Due to its broad spectrum, the volume contains often insightful and valuable contributions to the interdisciplinary and international body of scholarship that has emerged during the past 20 years.